Conformity Theory (Munasabah) In Ushul Fiqh - M. Jafar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the logic of Islamic law (qiyas) there is 'illat as the reason for establishing a law and justifying an analogy. Imam al-Ghazali included munasabah (conformity) in the category of his masalik al-'illah. Even in his work al-Mustasfa he is more focused and uses more the theory of munasabah as 'illat law. This can be seen clearly in his discussion of the qiyas chapter which was preceded as an introduction to the discussion of istislah (maslahah). Because munasabah has something to do with maslahah. In conformity theory (munasabah) there is al-awsaf munasab (appropriate attributes). Furthermore, this fate is divided into 3, namely: effective fate (mu'atstsir), harmonious fate (mula'im) and odd fate (gharib). Effective munasib (mu'atstsir) is an attribute that is known to be 'illat law based on the statement of the text or the existence of consensus. Munasib in harmony (mula'im) is an attribute that is known to be legal illat not because of a nas or ijmak statement, but because of its conformity with the law. The odd fate referred to by al-Ghazali is a fate that is not in harmony with the genus of law-making acts or there is no comparable example elsewhere.